Integration of time of use (TOU) tariff in net energy metering (NEM) scheme for electricity customers - Abdul Hafiz Razali; MD Pauzi Abdullah; Mohammad Yusri Hassan; Dalila Mat Said; Faridah Hussin (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
The introduction of Net Energy Metering (NEM) scheme for electricity customers in Malaysia is seen as an improvement from the previous Feed-In Tariff (FIT). However, the new NEM scheme only benefited the large residential customers but not to medium and small residential customers. Due to electricity tariff blocks structure, the large customers can avoid paying expensive tariff and hence reducing their electricity bill. This is not the case for medium and small customers since they are already paying lower tariff blocks due to their lower electricity consumption. This issue will discourage most residential customers to install solar PV system in their home and affect the Malaysia’s renewable energy target. This paper proposed a NEM scheme that integrates Time of Use (TOU) electricity tariff to the scheme. The proposed NEM-TOU scheme will be simulated, tested and compared to the new NEM scheme by using practical small, medium and large residential customers’ data. The results show that the proposed TOU-NEM scheme able to overcome the weakness of the current scheme where all customers (large, medium and low) can benefited by installing solar PV system in their home.